THE ANATOMY AND RELATIONSHIPS OF ENDENNASAURUS ACUTIROSTRIS (REPTILIA, NEODIAPSIDA), FROM THE NORIAN (LATE TRIASSIC) OF LOMBARDY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
A careful preparation of the holotype of Endennasautus acutirostris Renesto, 1984, that revealed part of the skull roof, along with the finding of a new specimen, allow a more complete description of the skeletal anatomy of this reptile and a better definition of its taxonomic position. The new specimen (paratype) is partially exposed from dorsal side (the holotype is exposed from the ventral side) and retains almost the entire tail, lacking in the holotype. Analysis of the newly available characters suggests close relationships between Endennasaurus and a group of Triassic marine reptiles, the Thalattosauria Merriam. Both Endennasaurus specimens were found in the Zorzino Limestone (Norian, Late Triassic), in the small quarry of Endenna, near Zogno, in the Bergamo Prealps (Lombardy, Northern ltaly).
Keywords: Endennasaurus acutirostris; Reptilia; Neodiapsida; Norian; Lombardy (Northern ltaly); Description; Systematic discussion.